2013
DOI: 10.1111/1574-6968.12133
|View full text |Cite
|
Sign up to set email alerts
|

1-Aminocyclopropane-1-carboxylate (ACC) deaminases fromMethylobacterium radiotoleransandMethylobacterium nodulanswith higher specificity for ACC

Abstract: The 1-aminocyclopropane-1-carboxylate (ACC) deaminases (EC 3.4.99.7), the key enzymes of degradation of the precursor of the phytohormone ethylene, have not been well studied despite their great importance for plant-bacterial interactions. Using blast, the open reading frames encoding ACC deaminases were found in the genomes of epiphytic methylotroph Methylobacterium radiotolerans JCM2831 and nodule-forming endosymbiont Methylobacterium nodulans ORS2060. These genes were named acdS and cloned; recombinant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Plant growth stimulation by endophytic bacteria is largely due to phytohormone production, and several studies have been reported the interaction of Methylobacterium species with different plant species by regulating phytohormone production [ 60 ]. Methylobacterium strains have been reported to produce phytohormones such as cytokinins and auxins [ 61 ], which promote cell division and elongation, respectively.…”
Section: Methylobacterium During Plant Interactmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant growth stimulation by endophytic bacteria is largely due to phytohormone production, and several studies have been reported the interaction of Methylobacterium species with different plant species by regulating phytohormone production [ 60 ]. Methylobacterium strains have been reported to produce phytohormones such as cytokinins and auxins [ 61 ], which promote cell division and elongation, respectively.…”
Section: Methylobacterium During Plant Interactmentioning
confidence: 99%
“…The acd S gene encodes an ACC deaminase enzyme that converts ACC into ammonia (NH 3 ) and α -ketobutyrate. An analysis of the genomes of Methylobacterium species revealed that the plant-associated species, such as M. oryzae , M. nodulans , and M. radiotolerans , contain this ACC deaminase gene [ 40 ] and that M. nodulans and M. radiotolerans are able to use ACC as a nitrogen source by the actions of ACC deaminase, reducing ethylene levels [ 60 ] and consequently the stress ethylene response in the host plant. Joe et al [ 68 ] reported that the association between an ACC deaminase-positive M. oryzae CBMB20 strain with Azospirillum brasilense CW903 strain reduced ethylene levels in plants.…”
Section: Methylobacterium During Plant Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the IRRB M. radiotolerans (B11) and the IRSB B. abortus (B15) present a high rate of failed predictions. It means that in most cases, M. radiotolerans is predicted as IRSB and B. abortus is predicted as IRRB; the former is an intracellular parasite (Halling et al, 2005) and the latter is an endosymbiont of most plant species (Fedorov et al, 2013). A probable explanation for these two failed predictions is the increased rate of sequence evolution in endosymbiotic bacteria (Woolfit and Bromham, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Bradyrhizobium japonicum is also able to degrade ACC through ACC deaminase production [71]. Recently, Fedorov et al [72] have characterized Methylobacterium nodulans ACC deaminase enzyme. ACC deaminase activity has also been demonstrated in members of -rhizobia, 4…”
Section: Acc Deaminase In Rhizobiamentioning
confidence: 99%